Addressing research questions in visceral leishmaniasis and post-kala-azar dermal leishmaniasis: Potential of reusing data from the Infectious Diseases Data Observatory platform - Prabin Dahal; Sauman Singh-Phulgenda; Dawit Getachew Assefa; Philippe J. Guerin (Annals of Medical Science and Research)
The Infectious Diseases Data Observatory (IDDO) data platform was launched in 2016 with the aim of harmonizing individual participant data (IPD) from clinical trials on infectious diseases, with a specific focus on neglected tropical diseases, including visceral leishmaniasis (VL). The VL data platform hosted by IDDO was developed in collaboration with researchers at the frontline of disease combat. This platform currently hosts IPD from more than 50 studies on VL and post-kala-azar dermal leishmaniasis (PKDL). The platform remains a controlled open-access repository to the scientific community and is currently facilitating collaborative IPD meta-analyses addressing research questions regarding drug safety and efficacy. Further open-access resources maintained by IDDO include clinical case report forms (CRFs) for VL, and VL-human immunodeficiency trials, a comprehensive inventory of all published VL clinical trials (1980–to date) and PKDL trials (1973–-to date), and these are publicly available as downloadable resources to the research community. These open-access resources developed in collaboration with the scientific community can help in identifying research gaps, and facilitate the generation of new evidence, and the CRFs can help to harmonize data collection for future trials. In this study, we highlight some of the ongoing and past research activities undertaken using these open-access resources (such as predictors of relapse and the development of a clinical scoring system for detecting relapse) and how these can support generating evidence to complement the ongoing activities in the Indian subcontinent and East Africa to reach the elimination targets.